Exogenous D-ribose promotes gentamicin treatment of several drug-resistant Salmonella - Zhou, Yanhong; Yong, Yan; Zhu, Chunyang; Yang, Heng; Fang, Binghu (Frontiers in Microbiology, 2022)
The metabolic microenvironment of bacteria impacts drug efficacy. However, the metabolic mechanisms of drug-resistant Salmonella spp. remain largely unknown. This study characterized the metabolic mechanism of gentamicin-resistant Salmonella Choleraesuis and found that D-ribose increased the gentamicin-mediated killing of this bacteria. Non-targeted metabolomics of homologous gentamicin-susceptible Salmonella Choleraesuis (SCH-S) and gentamicin-resistant S. Choleraesuis (SCH-R) was performed using UHPLC-Q-TOF MS. The metabolic signature of SCH-R included disrupted central carbon metabolism and energy metabolism, along with dysregulated amino acid and nucleotide metabolism, vitamin and cofactor metabolism, and fatty acid synthesis. D-ribose, the most suppressed metabolite in SCH-R, was shown to strengthen gentamicin efficacy against SCH-R and a clinically isolated multidrug-resistant strain. This metabolite had a similar impact on Salmonella. Derby and Salmonella. Typhimurium. D-ribose activates central carbon metabolism including glycolysis, the pentose phosphate pathway (PPP), and the tricarboxylic acid cycle (TCA cycle), increases the abundance of NADH, polarizes the electron transport chain (ETC), and elevates the proton motive force (PMF) of cells, and induces drug uptake and cell death. These findings suggest that central carbon metabolism plays a critical role in the acquisition of gentamicin resistance by Salmonella, and that D-ribose may serve as an antibiotic adjuvant for gentamicin treatment of resistant bacterial infections.